CD5 Controls Gut Immunity by Shaping the Cytokine Profile of Intestinal T Cells - Schuster, Cornelia; Kiaf, Badr; Hatzihristidis, Teri; Ruckdeschel, Anna; Nieves-Bonilla, Janice; Ishikawa, Yuki; Zhao, Bin; Zheng, Peilin; Love, Paul E.; Kissler, Stephan (Frontiers in Immunology, 2022)
CD5 is constitutively expressed on all T cells and is a negative regulator of lymphocyte function. However, the full extent of CD5 function in immunity remains unclear. CD5 deficiency impacts thymic selection and extra-thymic regulatory T cell generation, yet CD5 knockout was reported to cause no immune pathology. Here we show that CD5 is a key modulator of gut immunity. We generated mice with inducible CD5 knockdown (KD) in the autoimmune-prone nonobese diabetic (NOD) background. CD5 deficiency caused T cell-dependent wasting disease driven by chronic gut immune dysregulation. CD5 inhibition also exacerbated acute experimental colitis. Mechanistically, loss of CD5 increased phospho-Stat3 levels, leading to elevated IL-17A secretion. Our data reveal a new facet of CD5 function in shaping the T cell cytokine profile.